Sensitivity of Streptococcus pneumoniae isolated from clinical materials to oral antimicrobial agents - Narita, Hirokazu; Minami, Shinzaburou; Deguchi, Koichi; Maehana, Junko; Kitayama, Rieko; Horii, Taeko; Watanabe, Yasuo; Yasuda, Takashi (CHEMOTHERAPY, 1994)
We investigated the sensitivity of 40 strains of Streptococcus pneumoniae, which were isolated from clinical materials in Japan from 1982 to 1990, to various oral antimicrobial agents. There were 5 benzylpenicillin (PCG)-insensitive strains and no PCG-resistant strains. The MIC80s of cefteram and amoxicillin against the PCG-sensitive strains (35 strains) were the best and were followed by cefroxime, cefpodoxime>cefdinir>cefotiam>tosufloxacin, cefixime>sparfloxacin>levofloxacin, cefaclor>ciprofloxacin, ofloxacin, cephalexin>ceftibuten, minocycline>josamycin, erythromycin and clarithromycin. The MICs of amoxicillin, cefteram, cefroxime, cefpodoxime, cefdinir, cefotiam and tosufloxacin against PCG-insensitive strains (5 strains) were superior to those of other agents. Correlations between MICs of various β-lactams revealed that some strains became insensitive especially to cephems having an oxyimino or a 2-carboxyethylidene group on the 7-acyl side-chain.